Evaluation of Farming System research (FSr) on Small Livestock in West timor of East Nusa Tenggara - Fuah, A. M.; Petheram, J.; Priyanto, R. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2015)
Small livestock complement other parts of the agricultural system in West timor of East nusa tenggara (ntt), since crop residues, weeds and household wastes areavailable feed resources with low cost. the main roles are as farmers’ income and consumption, provide liquidity, have high value for ceremonies and cultural functions and are a store of wealth and family security. Pigs, goats and native chickens are comparatively important, with relatively large population. there is little published information on the farming systems in which they are kept, on their role, productivity, limitations or potential. Farming systems research (FSr) has been recognized by many government and international development agenciesas an appropriate approach in agricultural research and development, and the concept has been accepted by some organizations in Eastern Indonesia. However, there are few research programs in which an FSr procedure was followed, and evaluated for their effectiveness, especially in the context of livestock research and development. Evaluation of small livestock farming system research in West Timor, indicates that limitation in times and sufficient data at early stage , as well as broad information of target areas and farmers active involvement, became the main constraints in selecting appropriate location and sites for study purposes. the results of the general evaluation of one year research project suggested that FSr approach was appropriate, even for such a very small scale program. the level of progress achieved was largely dependent on the degree of institutional support provided by regional institutions. there was also need for having better understanding of FSr philosophy and methods for those involved in livestock research and development. Sucess of FSr depends largely on the degree and level of participation of farmers, research workers, and relevant specialists, including comittment of research workers, with close involvement with farmers, their families and problems.Key words: FSr, system approach, evaluation, small livestock